Comparison of protective effects of teneligliptin and luseogliflozin on pancreatic β-cell function: randomized, parallel-group, multicenter, open-label study (SECRETE-I study) - Shimoda, Masashi; Katakura, Yukino; Mashiko, Akiko; Iwamoto, Masahiro; Nakanishi, Shuhei; Anno, Takatoshi; Kawasaki, Fumiko; Obata, Atsushi; Fushimi, Yoshiro; Sanada, Junpei; Kohara, Kenji; Isobe, Hayato; et al. (Frontiers in Endocrinology, 2024)
Aims The aim of this study is to directly compare the effects of SGLT2 inhibitors and DPP-4 inhibitors on β-cell function in patients with type 2 diabetes. Materials and methods We conducted a 26-week, randomized, open-label, parallel-group study, including a 1-2 week drug washout period, in patients with type 2 diabetes with HbA1c ≥7.0% and <9.0% and BMI ≥20 kg/m2 despite treatment with a drug naïve or other than DPP-4 inhibitors or SGLT2 inhibitors. A total of 103 subjects were randomly assigned to receive once daily oral luseogliflozin (L) or teneligliptin (T). The primary endpoint was the effect of L vs. T on the change in logarithmus naturalis (Ln) disposition index (DI) (DI 0-120min; combining measures of insulin secretion and sensitivity) from baseline to week 25-26 (post intervention), which was calculated by conducting an oral glucose tolerance test. Results Ln DI 0-120min were improved in both groups: -0.46 ± 0.68 to -0.20 ± 0.59 (p=0.03) in L group and -0.26 ± 0.60 to -0.05 ± 0.62 (p=0.01) in T group. The change in Ln serum proinsulin/C-peptide ratio, a marker of β-cell dysfunction, was reduced in L group (1.63 ± 0.63 to 1.56 ± 0.68, p=0.16), but rather increased in T group (1.70 ± 0.75 to 1.90 ± 0.51, p=0.01), with significant difference between the two groups (-0.27; p=0.004). Conclusions Improvement of disposition index in subjects with obese type 2 diabetes was comparable between luseogliflozin and teneligliptin. On the other hand, it is likely that alleviation of β-cell dysfunction is more effective with luseogliflozin compared to tenegliptin. Clinical trial registration https://rctportal.niph.go.jp/en, identifier jRCTs061190008.